The Principle of Democracy in Albania, from the Basic Acts of the State in Its Implementation - Tafani, Ismail (European Journal of Multidisciplinary Studies, 2021)
The principle of democracy is seen as the basic pillar of the construction and function of a state. Of course, for the implementation of this principle, different ideologies have been developed, often in contradiction with each other. Ideologies which undoubtedly saw in the principle of democracy the birth and functioning of a state and as a consequence of a governing model which was to be based precisely on the sovereignty of the people and the full expression of its will. In Albania after the end of the Second World War we have the birth of a form of government which was based on the organization of the state according to communist theory. The communist ideology, which developed after the division of the world into two camps, which were the result of the Second World War meant to bring to Albania the realization of the principle of democracy. With the consolidation of the power of the communist party which resulted in the creation of the party-state, the principle of democracy consisted in its expression more as a slogan than as an objective for the development and functioning of society and the functioning of power as the genuine will of the people. Consequently, after the fall of the Berlin Wall, as in all former communist countries and in Albania, what the people demanded was the establishment of a state where the principle of democracy was the foundation of its government. Not in vain after the acceptance of political pluralism by the now completed monopoly of the party-state, the establishment of a system based on the principle of democracy was required. However, the creation of political pluralism after the change of the system does not seem to have brought a realization of the principle of democracy as a basis for the functioning of a democratic state as required by Albanian society. It can even be said that the principle of democracy remains an endless challenge for the entire political spectrum in Albania, although this principle always needs to be consolidated. Through this paper it is sought to analyze how the principle of democracy is required to be adopted by all leaders of any kind of government even though in itself it will have to belong to the people. This paper aims to highlight how in the case of political pluralism and even more so in the existence of a single party the principle of democracy remains a challenge, although it forms the basis of all fundamental acts of the Albanian State since the end of the Second World War.